Vulnerability versus opportunity: dissecting the role of low self-control and risky lifestyles in violent victimization risk among Korean inmates - Reyns, Bradford W. (Crime & delinquency, 2018)
The present study explores self-control, risky lifestyles, and domain-specific opportunities as explanations of violent victimization among adult male inmates from South Korea. Data were collected from the Inmate’s Conduct and Prison Security Survey in South Korea (N = 951). Structural equation modeling was used by applying a four-step process to examine the indirect effects of low self-control on prison victimization via risky lifestyles. We find that low self-control indirectly affects violent victimization via opportunities through risky lifestyles, and that risky lifestyles fully mediate the effect of low self-control on violent victimization in prison settings. Findings from the current study reinforce the contention that the relationship between low self-control and victimization includes a connection to opportunities for victimization. The results further suggest that the vulnerability that comes with possessing low self-control operates through the opportunities generated in living a risky lifestyle.